Gasoline Rationing in the United States, II - Maxwell, James A.; Balcom, Margaret N. (Quarterly Journal of Economics, 1946)
The Plan: the "A" Book, 125; the "B" Book, 127; preferred mileage, 129. — Special Rations: change of residence, 130; "hardship, " 132; furloughs, 133. — Fleet and Transport Rations: fleet, 133; transport, 134. — Non-highway Rations; Other Evidences: non-highway, 135; bulk and inventory coupons, 139; mihtary acknowledgments, 141. — Definition of Gasoline, 142. — The Flowback System and the Border Problem: the flowback system, 146; the border problem, 148. — The Black Market: invalidation cycles, 149; coupon endorsement, 151; mailing centers, 153. — The Effect on Consumption, 153.